Prenatal exposure to environmental phenols and childhood fat mass in the Mount Sinai Children's Environmental Health Study. (May 2016) - Buckley, Jessie P.; Herring, Amy H.; Wolff, Mary S.; Calafat, Antonia M.; Engel, Stephanie M.
Abstract: Early life exposure to endocrine disrupting chemicals may alter adipogenesis and energy balance leading to changes in obesity risk. Several studies have evaluated the association of prenatal bisphenol A exposure with childhood body size but only one study of male infants has examined other environmental phenols. Therefore, we assessed associations between prenatal exposure to environmental phenols and fat mass in a prospective birth cohort. We quantified four phenol biomarkers in third trimester maternal spot urine samples in a cohort of women enrolled in New York City between 1998 and 2002 and evaluated fat mass in their children using a Tanita scale between ages 4 and 9 years (173 children with 351 total observations). We estimated associations of standard deviation differences in natural log creatinine-standardized phenol biomarker concentrations with percent fat mass using linear mixed effects regression models. We did not observe associations of bisphenol A or triclosan with childhood percent fat mass. In unadjusted models, maternal urinary concentrations of 2, 5-dichlorophenol were associated with greater percent fat mass and benzophenone-3 was associated with lower percent fat mass among children. After adjustment, phenol biomarkers were not associated with percent fat mass. However, the association between benzophenone-3 and percent fat mass was modified by child's sex: benzophenone-3 concentrations were inversely associated with percent fat mass in girls (beta = − 1.51, 95% CI = − 3.06, 0.01) but not boys (beta = − 0.20, 95% CI = − 1.69, 1.26). Although we did not observe strong evidence that prenatal environmental phenols exposures influence the development of childhood adiposity, the potential antiadipogenic effect of benzophenone-3 in girls may warrant further investigation. Highlights: Quantified four phenol biomarkers in third trimester maternal spot urine samples Assessed percent fat mass at multiple follow-up visits between ages 4 and 9 years After adjustment, no association with 2, 5-dichlorophenol, bisphenol A, or triclosan Benzophenone-3 weakly associated with lower percent fat mass in girls only.